2020
DOI: 10.1021/acs.biomac.0c01198
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Reinforcement of Composite Hydrogels with Nanofiber Mixtures of Cellulose Nanocrystals and Chitin Nanofibers

Abstract: Simultaneous incorporation of cellulose nanocrystals (CNCs) and chitin nanofibers (ChNFs) into a polyvinyl alcohol (PVA) matrix opens possibilities for customization of more environmentally friendly composite materials. When used in tricomponent composite hydrogels, the opposite surface charges on CNCs and ChNFs lead to the construction of beneficial nanofiber structures. In this work, composite hydrogels containing CNCs, ChNFs, or their mixtures are produced using cyclic freeze–thaw (FT) treatments. When cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
2

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(34 citation statements)
references
References 49 publications
1
31
2
Order By: Relevance
“…After filling the void space of the template with a ChNF hydrogel, the template was dissolved in alkaline media (Figure a2), resulting in a ChNF system that retained the visual appearance of the original design (Figure a3) and led to an aligned internal porous structure (Figure a4). On the other hand, in order to control the interactions leading to nanofiber interconnections, a gas phase coagulation was applied by exposing the system to a volatile alkaline (e.g., ammonium hydroxide) or acid (e.g., hydrochloric acid) vapor, leading to physically cross-linked ChNF hydrogels containing PD-ChNF or TEMPO-ChNF (Figure b). Besides hydrogels produced from pure nanochitin, blending of nanochitin with other components allows composite hydrogels with enhanced performances. , For instance, loading alginate into a ChNC suspension improved the mechanical properties and swelling stability of the hydrogels due to strong electrostatic interactions between the nanocrystals and alginate molecules …”
Section: Applications Of Nanochitin In Multidimensional Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…After filling the void space of the template with a ChNF hydrogel, the template was dissolved in alkaline media (Figure a2), resulting in a ChNF system that retained the visual appearance of the original design (Figure a3) and led to an aligned internal porous structure (Figure a4). On the other hand, in order to control the interactions leading to nanofiber interconnections, a gas phase coagulation was applied by exposing the system to a volatile alkaline (e.g., ammonium hydroxide) or acid (e.g., hydrochloric acid) vapor, leading to physically cross-linked ChNF hydrogels containing PD-ChNF or TEMPO-ChNF (Figure b). Besides hydrogels produced from pure nanochitin, blending of nanochitin with other components allows composite hydrogels with enhanced performances. , For instance, loading alginate into a ChNC suspension improved the mechanical properties and swelling stability of the hydrogels due to strong electrostatic interactions between the nanocrystals and alginate molecules …”
Section: Applications Of Nanochitin In Multidimensional Materialsmentioning
confidence: 99%
“…619−621 Besides hydrogels produced from pure nanochitin, blending of nanochitin with other components allows composite hydrogels with enhanced performances. 622,623 For instance, loading alginate into a ChNC suspension improved the mechanical properties and swelling stability of the hydrogels due to strong electrostatic interactions between the nanocrystals and alginate molecules. 624 Although physical cross-linking generates nanochitin hydrogels with robust structures and strength, further enhancement of the performance and functions of nanochitin-based hydrogels requires chemical cross-linking, leading to covalently entangled networks.…”
Section: Gels and Three-dimensional Structuresmentioning
confidence: 99%
“…One of the effective approaches for enhancing the strength and self-healing simultaneously is to introduce appropriate fillers in the PB matrix. As a green-based reinforcement, cellulose fibers, particularly cellulose nanofibers (CNF), have been extremely appealing due to their plant-based biocompatibility and excellent mechanical properties. Accordingly, the fabrication of nanocomposite hydrogels via the addition of nanofillers such as CNF has been regarded as a trustworthy method. ,, The cellulose chains intrinsically assembled into unique hierarchical structures allow for advanced interactions between adjacent cellulose and polymer chains, contributing to the combined improvement of the mechanical property and self-healing performance. The design of stretchable, self-healing PB-based hydrogels with enhanced mechanical performance for biomimetic skin is essential for constructing desirable PB-based hydrogels as wound dressings.…”
Section: Introductionmentioning
confidence: 99%
“…Physical adsorption, for instance, by electrostatic interaction, facilitates nanoparticle adsorption at interfaces. 39 It has been demonstrated that food-grade Pickering emulsions can be stabilized by CNC electrostatically-modified with cationic surfactants; 40 however, to the best of our knowledge, no attempts have been attempted for CNF. Beyond this concept, rather than surfactants, and especially considering label-friendly products, particles or biopolymers bearing cationic charges can be combined with CNF.…”
Section: Introductionmentioning
confidence: 99%
“…Physical adsorption, for instance, by electrostatic interactions, facilitates nanoparticle adsorption at interfaces . It has been demonstrated that food-grade Pickering emulsions can be stabilized with CNC electrostatically modified with cationic surfactants; however, to the best of our knowledge, no attempts have been made for CNF.…”
Section: Introductionmentioning
confidence: 99%